Echocardiographic pulmonary hypertension probability is associated with clinical outcomes after transcatheter aortic valve implantation. (15th December 2016) - Nijenhuis, V.J.; Huitema, M.P.; Vorselaars, V.M.M.; Swaans, M.J.; de Kroon, T.; van der Heyden, J.A.S.; Rensing, B.J.W.M.; Heijmen, R.; ten Berg, J.M.; Post, M.C.
Abstract: Aims: Pulmonary hypertension (PH) is associated with mortality after transcatheter aortic valve implantation (TAVI). However, diagnosis based on tricuspid regurgitant velocity (TRV) is often inaccurate and unreliable. The updated PH guidelines introduced a PH probability grading implementing additional PH signs on transthoracic echocardiography (TTE), from which we aimed to analyse its effects on clinical outcomes in patients undergoing TAVI. Methods and results: We included 591 consecutive patients (mean age 80.2 ± 8.4 years, 58.0% female, mean STS risk score 6.2 ± 3.8%) undergoing TAVI. Patients were divided into "low" ( n  = 270; TRV ≤ 2.8 m/s without additional PH signs), "intermediate" ( n  = 131; TRV ≤ 2.8 m/s with additional PH signs, or TRV 2.9–3.4 m/s without additional PH signs), and "high" PH probability ( n  = 190; TRV 2.9–3.4 m/s with additional PH signs, or TRV > 3.4 m/s). The overall 30-day and 2-year mortality rates were 10.2% and 33.8%, respectively. "High" PH probability was an independent predictor of mortality at 30 days (HR 3.68, 95% CI 2.03 to 6.67, p  < 0.01) and 2 years (HR 2.19, 95% CI 1.57 to 3.04, p  < 0.01), compared to "low" PH probability. The "intermediate" group did not show an increased risk. The presence of additional PH signs resulted in a significantly higher mortality at 30 days (19.6% vs. 5.1%, p  < 0.01) and two years (54.2% vs. 22.5%, p  < 0.01). Conclusions: The updated echocardiographic PH probability model incorporating additional PH signs independently predicts early and late mortality after TAVI. Additional PH signs are of great value in assessing one's risks since its presence is strongly associated with early and late mortality.